Plasma and milk metabolomics revealed changes in amino acid metabolism in Holstein dairy cows under heat stress - E. Jorge-Smeding; Y.H. Leung; A. Ruiz-González; W. Xu; A.L. Astessiano; A.I. Trujillo; D.E. Rico; Á. Kenéz (Animal, 2024)
Our understanding of metabolic alterations triggered by heat stress is incomplete, which limits the designing of nutritional strategies to mitigate negative productive and health effects. Thus, this study aimed to explore the metabolic responses of heat-stressed dairy cows to dietary supplementation with vitamin D3/Ca and vitamin E/Se. Twelve multiparous Holstein cows were enrolled in a split-plot Latin square design with two distinct vitamin E/Se supplementation levels, either at a low (ESe−, n = 6, 11.1 IU/kg vitamin E and 0.55 mg/kg Se) or a high dose (ESe+, n = 6 223 IU/kg vitamin E and 1.8 mg/kg Se) as the main plot. Treatment subplots, arranged in a replicated 3 × 3 Latin square design, comprised heat challenge (Temperature Humidity Index, THI: 72.0–82.0) supplemented with different levels of vitamin D3/Ca: either low (HS/DCa−, 1 012 IU/kg and 0.73%, respectively) or high (HS/DCa+, 3 764 IU/kg and 0.97%, respectively), and a pair-fed control group in thermoneutrality (THI = 61.0–64.0) receiving the low dose of vitamin D3/Ca (TN). The liquid chromatography-mass spectrometry-based metabolome profile was determined in blood plasma and milk sampled at the beginning (day 0) and end (day 14) of each experimental period. The results were analyzed for the effect of (1) TN vs. HS/ESe−/DCa−, and (2) the vitamin E/Se and vitamin D3/Ca supplementation. No group or group × day effects were detected in the plasma metabolome (false discovery rate, FDR > 0.05), except for triglyceride 52:2 being higher (FDR = 0.03) on day 0 than 14. Taurine, creatinine and butyryl-carnitine showed group × day interactions in the milk metabolome (FDR ≤ 0.05) as creatinine (+22%) and butyryl-carnitine (+190%) were increased (P < 0.01) on day 14, and taurine was decreased (−65%, P < 0.01) on day 14 in the heat stress (HS) cows, compared with day 0. Most compounds were unaffected by vitamin E/Se or vitamin D3/Ca supplementation level or their interaction (FDR > 0.05) in plasma and milk, except for milk alanine which was lower (−69%, FDR = 0.03) in the E/Se+ groups, compared with E/Se−. Our results indicated that HS triggered more prominent changes in the milk than in the plasma metabolome, with consistent results in milk suggesting increased muscle catabolism, as reflected by increased creatinine, alanine and citrulline levels. Supplementing with high levels of vitamin E/Se or vitamin D3/Ca or their combination did not appear to affect the metabolic remodeling triggered by HS.